UJI AKTIVITAS EKSTRAK ETANOL DAUN PEPAYA (Carica papaya) TERHADAP WAKTU KEMATIAN CACING Ascaridia galli Schrank SECARA IN VITRO - Rina Widiastuti; Ana Mardiyaningsih; Yunisa Djayanti Putri (Universitas Muhammadiyah Semarang, 2015)
The prevalence of intestinal worms in Indonesia is still very high. Worming treatment can be performed using traditional medicine like papaya (Carica papaya). The purpose of this study to determine whether the ethanol extract of papaya (Carica papaya) concentration of 5% w / v, 10% w / v, 15% w / v has an influence on the time of death Ascaridia galli Schrank in vitro, knowing LC50 and LC90 , and knowing the chemical constituents in the ethanol extract of papaya (Carica papaya). Type of research is experimental because the use of treatment with the study design Posttest Only Control Groups Design. The sample used is Ascaridia galli Schrank females taken from chicken intestine. How it works in this research Ascaridia galli Schrank soak in a solution of NaCl 0.9% as negative control, a solution of piperazine citrate 0.9% as positive control, and a solution of ethanol extract of papaya (Carica papaya) with various concentrations. Each treatment group consisted of 15 worms were divided into five pots. Observations were made every 4 hours for 48 hours. Data were analyzed with the time of death worm SPSS 17 Kruskal Wallis method. Calculation LC50 and LC90 were analyzed by linear regression. Results of processing by Kruskal Wallis showed the ethanol extract of papaya (Carica papaya) concentration of 5% w / v, 10% w / v, and 15% w / v has an influence on the time of death Ascaridia galli Schrank in vitro. The results of calculations based on linear regression analysis showed LC50 ethanol extract of papaya (Carica papaya) at a concentration of 4.42% and LC90 at a concentration of 7.68%. Chemical identification results showed that ethanol extracts of leaves of papaya (Carica papaya) contain alkaloids, saponins, and tannins.Keywords: Carica papaya, Ascaridia galli Schrank.